Impact of Interim Dividend Announcements on Banking Stock Prices in India - Nadig, Asha (Indian Journal of Finance, 2017)
This study examined the stock market reaction to interim dividend announcements by Indian public sector banks in the year 2014. The year 2014 was the Indian parliamentary election year; there were a lot of expectations about dividends by the investing community. Not disappointing the investors, 22 of the 28 public sector banks declared interim dividends. This study analyzed the semi-strong efficiency of the Indian stock market with respect to interim dividend announcements by the banking companies in the year 2014. The methodology used for the study was market model event study. The results indicated that there were significant positive abnormal returns in some banking stocks prior to such announcements, signifying the investors were expecting such news and ,therefore, there was upward movement of stock prices. On the actual day of interim dividend announcement, 10 banks reacted positively on the announcement day, and 12 banks reacted negatively to the news.